ISSUES OF IMPLEMENTATION OF TERMS RELATED TO THE RAILWAY SECTOR IN THE ENGLISH LANGUAGE TEACHING PROCESS - Botirova , Nilufar Salimjon qizi (Innovative Development in Educational Activities, 2023)
this article analyzes the process of working with the terminology of the railway sector in the educational process by future specialists. The classification of terms related to the railway industry and the procedure for its application are highlighted. English railway terminology is distinguished by content and structural features, forming part of the language lexical from the linguistic point of view. The methodology of teaching a foreign language is an integral part of linguodidactics and is thought about the importance of their linguistic features in the teaching of terms.